PENGARUH MODEL ADVANCE ORGANIZER DENGAN PETA KONSEP TERHADAP SIKAP SISWA SMP DALAM PEMBELAJARAN MATEMATIKA - Mellawaty (Universitas Wiralodra, 2017)
Attitude is one focus of learned process. But in reality they have a negative certain attitude to mathematics attented clases. One alternative learning that can improve attitude students is a model Advance Organizer with a concept map. This study aims to determine the increase in mathematics attitude of students who received Advance Organizer model learning with concept maps and students who obtain teaching expository method. This study used an experimental method. The population in this study were students of class VII SMP Negeri 1 Kroya Indramayu and taken two classes at random according to the class as a sample. Instruments used in this research is non-test. Based on the analysis of research data, we concluded that, by enhancing the mathematics attitude of students who obtain a mathematical model study Advance Organizer to map the concept positive than students who received learning expository method.